2018
DOI: 10.1177/1087054718769149
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Visual and Auditory Stimuli in Continuous Performance Tests: Differential Effects on Children With ADHD

Abstract: Auditory parameters in the inattention domain (OE and VRT) can discriminate ADHD from controls. For the hyperactive/impulsive domain (CE), the two modalities are equally important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
(55 reference statements)
0
21
0
Order By: Relevance
“…In this regard, Egeland and Kovalik-Gran (2010) found correlations between the CPT variables and the attention subdomains. More recently, Schmidt et al (2016), Simões et al (2017), and Simões et al (2018a) have reported that attention–deficit–disorder (ADHD) patients exhibit particular deficits on CPT variables. Simões et al (2018b) further demonstrated that these deficits were associated with different attention subdomains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Egeland and Kovalik-Gran (2010) found correlations between the CPT variables and the attention subdomains. More recently, Schmidt et al (2016), Simões et al (2017), and Simões et al (2018a) have reported that attention–deficit–disorder (ADHD) patients exhibit particular deficits on CPT variables. Simões et al (2018b) further demonstrated that these deficits were associated with different attention subdomains.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the Continuous Visual Attention Test (CVAT) is commonly used for attentional assessments (Schmidt et al, 2008, 2016, 2017; Avellar et al, 2016; Simões et al, 2017; Simões et al, 2018a, b). The CVAT is a typical Go/No-go task approved for clinical use in Brazil that does not depend on IQ, has robust internal consistency and construct validity, as well as a high test–retest reliability (Schmidt and Manhães, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Egeland and Kovalik-Gran ( 28 ) found correlations between CPT variables and attention subdomains. More recently, Simões et al ( 29 ) and Schmidt et al ( 30 ) have reported that ADHD patients exhibit particular deficits on CPT variables. These authors further demonstrated that the deficits were associated with different attention subdomains.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the continuous visual attention test (CVAT) is a typical CPT validated for clinical use in Brazil ( 31 ). The CVAT has extensively been used in several neurological disorders such as ADHD ( 29 , 30 ) and chronic pain fibromyalgia ( 32 ). It does not depend on the patient's IQ and there is no learning effect during retests.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the difference between primary auditory and visual perceptual systems, attention may be modality specific (Khaleghi, Zarafshan, & Mohammadi, 2019; Waddington et al, 2018). Some investigations have simultaneously obtained visual and auditory attention profiles for patients with ADHD (Moreno-Garcia, Delgado-Pardo, & Roldan-Blasco, 2015; Schmidt, Simoes, & Novais Carvalho, 2019; Simoes, Carvalho, & Schmidt, 2018). Lin et al (2017) used the Test of Variables of Attention (TOVA) as a primary assessment tool and found that the impairment of visual attention is more serious than that of auditory attention in children with ADHD.…”
Section: Introductionmentioning
confidence: 99%